Antisymmetry and word order in double object constructions in Zarma - Jayeola, Waheed Ayisa (Linguistik Online, 2020)
Double Object Construction in Zarma sometimes allows alternations in the order of its internal arguments and the order in some cases may also be fixed. This tendency does not make predictions about a canonical order for the occurrence of Theme and Recipient objects within the VP simple. The same condition applies to monotransitive structures which vary between a complement-head and a head-complement order. It is the aim of this paper to present and analyse the most salient features of the kind of variations found in Zarma word order, particularly the ones associated with the verb that encodes three-participant events. The paper adopts the minimalist program proposed by Chomsky and is complemented with the Antisymmetry Hypothesis proposed by Kayne (1994). The study shows that the language has a uniform linear order where the recipient canonically precedes the theme on the basis of animacy factor. This is particularly common with the pronoun as the recipient in double object structures. Employing different diagnostics, the paper concludes that the recipient only follows the theme when the theme is associated with a more prominent discourse status. It is also argued that asymmetric C-command always occurs between the theme and the recipient. It implies that the language symmetry is altered by movement to designated positions for the purpose of feature checking.